Pigmented Free-Floating Posterior Vitreous Cyst - Claudia Bruè; Cesare Mariotti; Edoardo De Franco; Nicola De Franco; Alfonso Giovannini (Case Reports in Ophthalmological Medicine)
Vitreous cysts are very rare ocular malformations. In this observational case study, we report on an unusual case of a pigmented free-floating vitreous cyst and discuss its differential diagnosis. A 14-year-old male was referred to ophthalmology for a pigmented lesion in his left eye. He complained of an intermittent floater in the left eye. Visual acuity was 20/20 in the right eye and 20/40 in the left eye. Fundus examination was unremarkable bilaterally, except for a piece of brownish oval material floating in the vitreous in the left eye. He had received a knock on the left side of his head a few days before the visual discomfort of the left eye. Real-time ultrasound of the left eye detected a piece of hyperechogenic spherical material with no internal reflectivity, floating in the middle of the vitreous. The first use of color Doppler ultrasound in this context indicated no arterial flow, ruling out the presence of a persistent hyaloid artery. Intraocular cysts are rare ocular disorders, which have been divided into clear and pigmented cysts, and into those that occupy the anterior chamber, the retrolental space, and the vitreous cavity. This last is extremely rare. We describe such a case.